THE ROLE OF THE COMMUNITY IN LAW ENFORCEMENT ERADICATION OF CORRUPTION CRIME - Sri Wulandari (Universitas Negeri Semarang, 2019)
The aspirations of the community in eradicating criminal acts of corruption are very much needed and have an important role as social control. Therefore, efforts to prevent and eradicate corruption need to be intensified by continuing to uphold human rights and the interests of society. Law Number 20 Year 2001 concerning Amendment to Law Number 31 Year 1999 concerning Eradication of Corruption, formulating it explicitly as a formal crime means that even though the results of corruption have been returned to the perpetrators' countries, they are still submitted to the court and the judicial process applies the burden of proof in reverse. which is limited or balanced. It turns out that in this Law the defendant's statement is not a strong evidence because it is only a means of supporting existing evidence, this provision actually becomes a weakness in eradicating criminal acts of corruption. Because the position of a strong defendant's information will become evidence legal and legal basis for judges to impose a crime.